Demographic Profile of Knee Osteoarthritis Patients in a Teaching Hospital West Java, 2013 - Nugrahaputra, Tranggana; Prabowo, Tertianto; Sadeli, Henny Anggraini (Althea Medical Journal, 2015)
Background: Osteoarthritis is the most common degenerative musculoskeletal diseases occur worldwide.Â It usually affects the weight-bearing joint such as knee and vertebra. Osteoarthritis is influenced by variousÂ risk factors. The aim of the study was to identify the demographic profile of knee osteoarthritis patients.Methods: A retrospective descriptive study was performed to 247 medical records of knee osteoarthritisÂ patients who attended to Physical Medicine and Rehabilitation of Dr. Hasan Sadikin General HospitalÂ Bandung in 2013. The inclusion criteria were medical records that consisted of age, sex and occupation ofÂ the patients, and payment methods. Exclusion criteria were incomplete of the necessary data mentioned inÂ the inclusion criteria. The study was conducted from August until November 2014. The collected data wereÂ analyzed and presented using frequency distribution.Results: From all the patients, 40.9% was 60-69 years old, 77.7% were women and 82.6% were retiredÂ patients. Most of the patients had a social health insurance.Conclusions: Majority of patients is 60â69 years old women, retired and has the financial protection.Â [AMJ.2015;2(4):597â600]Â DOI:Â 10.15850/amj.v2n4.468